The influence of career guidance on career orientation among vocational college students in China - Zhiwei, He; Siew Ping, Wong (Journal of Islamic, Social, Economics and Development, 2025)
This study investigates the role of career guidance in shaping career orientation among vocational college students in China, with a focus on the effectiveness of personalized counseling, aptitude testing, and access to industry information. The study employs a quantitative approach, collecting data from 385 students across three vocational institutions. The research aims to explore how career guidance influences students' career decision-making processes and how effectively it aligns their career aspirations with the labor market demands. Data were collected through online surveys and analyzed using Pearson’s correlation coefficient and multiple regression analysis. The findings reveal that personalized counseling has the most significant impact on students’ confidence in their career choices, followed by aptitude testing and industry-specific information. This study highlights the importance of career guidance in vocational education and underscores the need for improvements in service delivery to better meet the diverse needs of students. The results provide valuable insights for vocational colleges in China, suggesting that enhancing the quality and accessibility of career guidance services can significantly contribute to students' successful transition from education to employment. These findings offer practical recommendations for educational institutions to optimize career guidance programs, ensuring that students are better prepared for the workforce and equipped to navigate the complexities of their future careers.